Ṭhākurabāṛira andara mahala - Deb, Chitra, 1946- (Ānanda, 1980)
On the women of the Tagore family; their impact on the traditional life of Bengali Hindu women and their contribution to the 19th century renaissance in Bengal with special reference to women.